DDRE-30. CELL-PENETRATING PEPTIDE ANTAGONIST OF CCAAT/ENHANCER BINDING PROTEIN ß DISPLAYS POTENT ANTI-GLIOBLASTOMA ACTIVITY. (12th November 2021) - Rotolo, Jim; Ghamsari, Lila; Ramierez, Ricardo; Koester, Mark; Leong, Siok; Gallagher, Erin; Darvishi, Emad; Merutka, Gene; Kappel, Barry
Abstract: CCAAT/Enhancer Binding Protein Beta (C/EBPß) is a transcription factor overexpressed in glioblastoma (GBM). Mechanistically, C/EBPß is a master regulator of mesenchymal transition in GBM, and its increased expression correlates with mesenchymal differentiation and predicts poor clinical outcome. C/EBPß activity requires dimerization with co-factors such as CREB/ATF family members via leucine zipper interactions. ST101 is a novel peptide antagonist of C/EBPß currently being evaluated in a Phase 1/2 clinical study in patients with advanced unresectable and metastatic solid tumors. ST101 binds to the C/EBPß leucine zipper, thereby preventing dimer formation and inhibiting its transcriptional activity, resulting in selective tumor cell cytotoxicity. Here, we describe ST101 non-clinical anti-tumor activity against GBM. In vitro studies in T98G and U251 cells demonstrate ST101 dose-dependent impact of cell viability (EC50 of 2.2 and 1.2 μM, respectively), accompanied by significant impact on C/EBPß-mediated gene expression as determined by qPCR analysis. In contrast, normal human mononuclear and epithelial cells were not sensitive to ST101 (EC50 > 80 μM). In vivo, ST101 displayed significant anti-tumor activity in a U251 GBM subcutaneous xenograft model, resulting in 81.4% tumor growth inhibition (TGI) vs. control and undetectable tumors in 50% of animals. Following ST101 exposure tumors displayed reduced BIRC3 and ID2 gene expression, and significantly increased cleaved caspase 3 immunostaining indicative of cell death induction. In U251 tumors, subtherapeutic ST101 (< 5% TGI) in combination with temozolomide (< 5% TGI) resulted in 52.8% TGI, significantly greater than either single-agent alone. Similarly, in a temozolomide-refractory T98G GBM subcutaneous xenograft model, ST101 (41.6% TGI) in combination with TMZ (< 5% TGI) resulted in significant anti-GBM response (72.4% TGI). These data emphasize the potential of ST101 as a potent peptide therapeutic for GBM.